Impact of Mid-Season Drought on Tuber Yield, Biomass, Harvest Index, and Water-Use Efficiency of Jerusalem Artichoke in Tropical Regions - Ruttanachira Ruttanaprasert; Sanun Jogloy; Thanawat Kaewkhieo-Ngam; Anon Janket; Ratchanee Puttha; Chorkaew Aninbon (My University, 2025)
Mid-season drought is increasingly recognized as a major constraint on tuber production in Jerusalem artichoke. The ability of different genotypes to maintain high yields under such conditions is a critical component of drought tolerance. This study aimed to investigate the effects of mid-season drought on tuber yield, biomass, harvest index, tuber water-use efficiency (WUEt), and biomass water-use efficiency (WUEb) across various Jerusalem artichoke genotypes with differing levels of drought tolerance. The experiment was conducted in pots using a 2 × 5 factorial combination in a randomized complete block design with four replications over two years. Factor A consisted of two water regimes: field capacity (FC) and mid-season drought. Factor B included five genotypes: JA 3, JA 125, JA 15, JA 89, and CN 52867. Mid-season drought significantly reduced tuber dry weight, biomass, WUEt, and WUEb, while increasing the harvest index. Significant differences were observed among genotypes for tuber dry weight, biomass, harvest index, WUEt, and WUEb under both water regimes. CN 52867 and JA 89 were characterized as drought-tolerant genotypes with high water-use efficiency and high yield potential. JA 3 was also noted for its lower yield reduction under stress. These three genotypes serve as valuable genetic resources for breeding programs aimed at developing progeny populations with enhanced yield potential and drought tolerance, particularly for mid-season drought-prone environments.
Keywords: Jerusalem artichoke; Drought Resistance; Microbial Metabolites in Food Biotechnology